EFEKTIVITAS MENGGAMBAR 3D MODEL AUTODESK INVENTOR MENGGUNAKAN JOB SHEET TERSTRUKTUR - Rizky Wijanarko; setuju; Alfat Khaharsyah (JURNAL VOKASI DEWANTARA (JVD), 2025)
This study aims to (1) compile the E-Module for the Manufacturing Drawing Engineering subject on CAD material using the Autodesk Inventor Pro 2021 Software class XI at SMK Muhammadiyah Prambanan, (2) determine the feasibility of the E-Module for the Manufacturing Drawing Engineering subject on CAD material using Software Autodesk Inventor Pro 2021 class XI at Prambanan Muhammadiyah Vocational School. This research is included in research and development (Research and Development). The development of this research uses a 4D development model. This research and development model consists of define, design, development, and dissemination sessions. The subjects in this research consisted of module experts and media experts, namely PVTM Yogyakarta study program lecturers, and class XI students majoring in Machining Methods at the Muhammadiyah Prambanan Vocational High School (SMK) as media users who grew up. The research object is intended for teaching materials. Methods of collecting information using questionnaires and observation. Information analysis method using descriptive quantitative. The results of this research are educational media in the form of an E-Module of the Manufacturing Photo Method in the CAD module using the Autodesk Inventor Pro 2021 Application. The development of learning media is said to be good and of high quality, and overall the average score obtained is 3.41 with a feasibility percentage of 85%. included in the very good criteria. The developed module is effectively used as teaching material in manufacturing drawing engineering subjects.